Ответ:
х = -17/18
Пошаговое объяснение:
-3(-3-2x) = -5(6x+5)
9 + 6х = -30х - 25
6х + 30х = -25 - 9
36х = -34
х = -34/36
Проверка:
-3((-3 - 2*(-17/18)) = -5((6*(-17/18) + 5))
-3(-3 + 17/9) = -5(-17/3 + 5)
-3 * (-10/9) = -5 * (-2/3)
30/9 = 10/3
10/3 = 10/3
3 1/3 = 3 1/3 - верно
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
х = -17/18
Пошаговое объяснение:
-3(-3-2x) = -5(6x+5)
9 + 6х = -30х - 25
6х + 30х = -25 - 9
36х = -34
х = -34/36
х = -17/18
Проверка:
-3((-3 - 2*(-17/18)) = -5((6*(-17/18) + 5))
-3(-3 + 17/9) = -5(-17/3 + 5)
-3 * (-10/9) = -5 * (-2/3)
30/9 = 10/3
10/3 = 10/3
3 1/3 = 3 1/3 - верно